Deadly currents [large type] - Goddard, Elizabeth (Goddard, Elizabeth. Hidden Bay, 2026)
"Investigative journalist Cressida Dane arrives in Hidden Bay after a worldwide journey to finish her late father's manuscript on shipwrecks. As she tries to discover the story behind the "ghost ship" Specter's Bounty, her only lead is a name her father left behind--Evelyn Monroe. As Cressida uncovers more about the ship, she quickly realizes that her research has placed her in the crosshairs of dangerous forces. County detective Braden Sanders is in Hidden Bay for one reason--to get his niece lifesaving medical treatment. To do that, he is assigned to protect Cressida from a revenge-driven enemy. Together, Braden and Cressida dig deeper to discern the myth from the facts surrounding the Specter's Bounty. But more is brewing under the surface than they could ever imagine. Entangled in secrets, they must unravel the past before the current sweeps away their future."--